Water Quality, Biometric Indices and Hematological Investigation of Farm-reared Thai Silver Barb, Barbonymus gonionotus in Spring (Research in Agriculture Livestock and Fisheries, 2026)
Studies were conducted to determine water quality, biometric indices, and hematological parameters of farm-reared Thai silver barb (Barbonymus gonionotus) in the pre-spring, spring, and post-spring seasons. A total of 90 fish (average: 73.16±19.45 g) were randomly collected from Reliance Aqua Farm (Ukilbari, Boilor, Trishal) and M/s Char Bhai Hatchery and Fish Farm (Shomvuganj, Mymensingh sadar) located in Mymensingh district. Corresponding water samples were collected from the respective ponds, and water temperature, DO, pH, and NH3 were determined immediately. The experiment was conducted in the Fish Disease Laboratory, Department of Aquaculture, Bangladesh Agricultural University. The bacterial loads of pond water (CFU/mL) were determined by ten-fold serial dilution in duplicates on Tryptone soya agar (TSA) after incubation at 37°C for 24 hrs. Hematological and hemato-biochemical analyses of blood samples, viz., total RBC, total WBC, hemoglobin, blood glucose level, ESR, PCV, MCH, MCV, MCHC, and DLC, were performed, and data were analyzed statistically. The length and weight of B. gonionotus were measured, and the following biometric indices were calculated and analyzed: LWR, condition factor (K), and VSI. Findings showed that DO and pH levels increased with increasing water temperature, but NH3 remained constant throughout the study period. The highest average bacterial load was 10.58±0.1.42×103 CFU/mL in pre-spring, while the lowest average load was 6.7±0.65×103 CFU/mL in the post-spring season. ESR, MCV, glucose, total WBC, and granulocytes were found to be higher at low temperatures, and PCV, MCH, MCHC, Hb, RBC, and monocytes were recorded to be higher at high temperatures. The study showed negative allometric growth during the pre-spring period, but positive allometric growth during the spring and post-spring periods. The findings revealed baseline hematobiochemical information on the farm-reared Thai silver barb in the spring season, which will be helpful for sustainable production and for reinforcing proper health management strategies at the farm level.Res. Agric. Livest. Fish. Vol. 13, No. 1, April 2026: 197-217